A Learning Needs Analysis of PAI for Strengthening Qur’anic Literacy at Vocational High School - Irdiantina, Shasy Suci; Sulistiono, Muhammad; Musthofa, Indhra (Al Ulya: Jurnal Pendidikan Islam, 2026)
Islamic Religious Education plays a strategic role in shaping students’ religious character, particularly through mastery of Qur’anic reading and writing skills (BTQ), which serve as the foundation of religious learning. However, at the vocational high school level, disparities in students’ basic BTQ abilities persist, affecting the effectiveness of Islamic Religious Education learning. Previous studies have largely emphasized the use of learning media or digital approaches in religious education, while studies that specifically analyze the learning needs of BTQ and its integration with the school’s academic system remain limited. This study aims to analyze the learning needs of Islamic Religious Education in improving students’ Qur’anic reading and writing skills at SMK Negeri 1 Kepanjen, Malang. This research employs a descriptive qualitative approach with a case study design. Data were collected through semi-structured interviews with one Islamic Religious Education teacher, observations of the learning process, and documentation studies, and were analyzed using the interactive model of Miles and Huberman, which includes data condensation, data display, and conclusion drawing. The results show that the main need in Islamic Religious Education learning lies in strengthening students’ basic BTQ abilities, which are still uneven in both reading and writing Arabic letters. Observation and interview findings indicate that some students still have difficulty reading the Qur’an fluently and writing Arabic letters correctly. To address this condition, the school developed a learning innovation through the Qur’an Reading Completion Program (Tuntas Baca Al-Qur’an) integrated into the school’s academic system through the use of pocket books, recitation submissions, and the gradual strengthening of reading and writing practice, which helps teachers monitor the development of students’ BTQ abilities more systematically. This study concludes that strengthening BTQ should be designed in an adaptive, tiered, and sustainable manner as a strategic component of Islamic Religious Education.